An Exploring the Relationship Between Consumer Knowledge and Adoption of Energy-Efficient Home Technologies - Ankur Lohiya, Vivek Aggarwal, Anjali Dixit, Rashi Srivastav, Sameer Yadav, Mohd Aarif (Journal of Informatics Education and Research, 2023)
This research delves into the intricacies of consumer attitudes towards energy efficiency in household appliances, scrutinizing the nexus between awareness levels, preferences, and gender disparities. Employing descriptive research methods, the study embraces a sample population of 200 participants in India, employing Taro Yamane's formulas to ascertain an optimal sample size. Implementing Stratified Random Sampling, the research probes independent variables, including awareness levels, preferences for energy-efficient appliances, and demographic factors. Dependent variables encompass the level of awareness, preference models, and the willingness to pay a premium. Data collection encompasses primary methods like surveys and focus groups, complemented by secondary data from diverse sources. The outcomes unearth a noteworthy divergence in awareness scores between consumers cognizant and unaware of energy-efficient appliances. Moreover, gender-based distinctions wield substantial influence over preferences for energy-efficient home appliances, with female participants exhibiting higher preference scores than their male counterparts. The research solidifies the reliability of the employed research variables through Cronbach's Alpha. The findings underscore the imperative of gender-specific considerations in shaping consumer preferences for energy-efficient technologies. The study furnishes pivotal insights for policymakers, marketers, and researchers striving to augment the assimilation of sustainable technologies in households.